Immobilization and Stabilization of Aspergillus Fumigatus α-Amylase by Adsorption on a Chitin - Yandri Yandri; Ezra Rheinsky Tiarsa; Tati Suhartati; Bambang Irawan; Sutopo Hadi (Ital Publication, 2023)
In this research, immobilization of A. fumigatus α-amylase on chitin was studied with the main purpose to improve the characteristics of the enzyme. A series of experiments were carried out to study stability improvement, thermodynamic parameters, include ki, ΔGi, and t½, and reusability of the immobilized enzyme. The experimental results indicate that significant thermal stability was achieved, as indicates by the ability of the enzyme to retain its relative activity above 39% after 80 min of incubation at 60oC. Thermodynamic parameters, include ki, ΔGi, and t½, indicate that the immobilized enzyme is more rigid, stable, and less flexible in the water, resulting in increased stability up to 1.5 times compared to that of the native enzyme. Furthermore, the immobilized enzyme was able to retain over 46% of its initial activity after six consecutive applications for starch hydrolysis, confirming the potential of chitin for the production of immobilized enzymes on an industrial scale. Doi: 10.28991/ESJ-2023-07-01-06 Full Text: PDF